Fishery and biology of Paphia malabarica from Dharmadom estuary, north Kerala - Thomas, Sujitha; Laxmilatha, P; Nasser, M; Surendranath, V G; Ramachandran, N P; Sivadasan, M P (Indian Journal of Fisheries, 2011)
The short neck clam, Paphia malabarica forms a part of the bivalve fishery of Dharmadom estuary. Average annual catch during the period 2000-2002 was estimated to be 2.49 t. Peak fishing during the period was in October. P. malabarica of length range 18-50 mm contributed to the catch. Male dominated the catch except in January, August and November. Percentage of mature clam was found to be high during November to February indicating spawning period in these months with peak spawning activity in November - December.